Evaluation of ChatGPT Usage in Preschool Education: Teacher Perspectives - Ugras, Mustafa (My University, 2024)
This study aims to determine teachers’ views on the use of ChatGPT in preschool education. The study was conducted using a case study, which is one of the qualitative research methods. In the 2023–2024 academic year, the study group consisted of 16 preschool teachers working in a province in the Eastern Anatolia Region of Turkey. The researcher developed a semi-structured interview form and used researcher diaries as data collection tools. An inductive content analysis approach described the data from the interviews with the participating teachers and the research diaries. The findings revealed that most of the teachers thought that ChatGPT was suitable for preschool education due to its potential, such as creating personalized and creative activities and suggesting games and stories. However, negative opinions about potential problems such as obtaining misinformation, technology addiction, decreased social interaction, and deriving age-inappropriate content were also identified. For successful integration at the pre-school level, technical requirements such as tablets and computers may be needed, as well as teacher trainings, a guide on how to use ChatGPT effectively, and information for parents. School administrators, teachers, and parents should receive training about ChatGPT, as suggested.
Keywords: Artificial intelligence (AI); Early childhood; Preschool teachers; ChatGPT; Kindergarten